2018
DOI: 10.1149/2.0231808jes
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Monitoring of Wound Healing Using a Wearable Enzymatic Uric Acid Biosensor

Abstract: Wound management involves repeated clinical trips and procedures of lab tests over days. To eliminate this time lag and provide real-time monitoring of a wound's progress, we have designed an enzymatic biosensor for determining uric acid (UA) in wound fluid. Uric Acid is a biomarker, having an established correlation with wounds and their healing. This electrochemical biosensor comprises enzyme urate oxidase (uricase, UOx) entrapped in a polyvinyl alcohol based cationic polymer for enhanced stability. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 46 publications
2
60
0
Order By: Relevance
“…They compare performance of classification algorithms by comparing their accuracy, sensitivity and response time and concluded that decision trees and K-nearest neighbor outperforms other algorithms. Sohini Roy Choudhury et al [21] design wearable device to monitor wound healing with help of uric acid biosensor. Their proposed device detects Uric Acid(UA) from wound.…”
Section: State Of the Artmentioning
confidence: 99%
“…They compare performance of classification algorithms by comparing their accuracy, sensitivity and response time and concluded that decision trees and K-nearest neighbor outperforms other algorithms. Sohini Roy Choudhury et al [21] design wearable device to monitor wound healing with help of uric acid biosensor. Their proposed device detects Uric Acid(UA) from wound.…”
Section: State Of the Artmentioning
confidence: 99%
“…Sohini Roy Choudhury et al [13] designed wearable device to monitor wound healing with the help of a uric acid biosensor. Their proposed device detected Uric Acid (UA) from the wound.…”
Section: Features and Limitations Of Previous Researchmentioning
confidence: 99%
“…The matrix value showing the total predicted "favourable" classes was 89, out of which one class was truly unfavourable and wrongly predicted to be favourable, while the total unfavourable classes were 145, out of which 116 were predicted correctly, and 29 were truly favourable, but predicted to be unfavourable. By the given confusion matrix of the accuracy and error rate for both classes, prediction could be measured with the help of the formulae given in Equations (12) and (13).…”
Section: Evaluation Of the Trained Svm Classifiermentioning
confidence: 99%
See 1 more Smart Citation
“…Such sensor could become the basis of a POC device for chronic wound care. Several sensors to assess wound healing progression have been developed, targeting infection, pH, oxygen, uric acid, hemoglobin, and broad-spectrum proteases (Dargaville et al, 2013;Edwards et al, 2013;Sharp, 2013;Krismastuti et al, 2014Krismastuti et al, , 2015aKrismastuti et al, , 2017Ochoa et al, 2014;Salvo et al, 2015;Jankowska et al, 2017;RoyChoudhury et al, 2018). These sensors have not reached yet the stage of deployment in the clinic due to the challenges involved, such as the complex wound environment with hundreds of proteins present in a wide pH range.…”
Section: Introductionmentioning
confidence: 99%